Generation of Magnetic Fields around Black Hole Accretion Disks due to Nonconservative Radiation Fields - Mukesh Kumar Vyas; Asaf Pe’er (The Astrophysical Journal Letters)
We investigate the generation of magnetic fields above black hole accretion disks due to the nonzero curl of the disk radiation field. By self-consistently computing the components of the radiation flux and their curl, we show that the rotational nature of the radiation field induces charge separation, leading to magnetic field generation in the plasma above the disk. Solving the magnetohydrodynamic equations, we derive the time evolution of these fields and demonstrate that they grow over astrophysically relevant timescales. For a standard Keplerian accretion disk, the produced magnetic fields remain weak, on the order of a few gauss, consistent with previous predictions. However, when a luminous corona is present in the inner disk region ( r _d  < 3 r _g –10 r _g ), the generated fields reach dynamically significant strengths of up to 10 ^5 G, where the magnetic energy density approaches a few percentage of gas pressure. These fields develop within realistic growth timescales (such as the viscous timescale) and can be dynamically significant in governing disk and jet evolution. Our findings suggest that radiation-driven magnetic fields play a crucial role in accretion flow magnetization, influencing both disk dynamics and observational signatures. The predicted field strengths could affect the thermal emission, synchrotron radiation, and polarization properties of black hole accretion systems, with implications for X-ray binaries, active galactic nuclei, and jet formation. Future numerical simulations and high-resolution polarimetric observations, such as those from the Imaging X-ray Polarimetry Explorer, enhanced X-ray Timing and Polarimetry Mission, and the Event Horizon Telescope, may provide observational confirmation of our findings.